Strategies for Sustainable Financing of Secondary Education in Sub-Saharan Africa - Lewin, Keith M. (Washington, DC : World Bank, 2012)
This thematic study discusses strategies for sustainable financing of secondary education in Sub-Saharan Africa. The report provides insight into options for financing the expansion of secondary education and training in Africa. This comes with a hefty price tag and points to the need to undertake fundamental reforms swiftly. This publication messages are clear: secondary education and training in Sub-Saharan Africa faces the challenge of improved efficiency and improved quality simultaneously with a fast growing demand. Sustainable financing will also require more effective public-private partnerships, because governments have many priorities and do not have a lot of room for significant additional public funding of post-primary systems. Educational reforms are needed to expand enrollment in secondary schooling in affordable ways. These reforms will contribute to poverty reduction by increasing the levels of knowledge, skills, and capability; diminishing inequalities in access that limit social mobility and skew income distribution; and contributing to the achievement of the Millennium Development Goals (MDGs) that relate to education.